Chronic high-altitude exposure and the epidemiology of ischaemic stroke: a systematic review. Issue 4 (29th April 2022) - Ortiz-Prado, Esteban; Cordovez, Simone Pierina; Vasconez, Eduardo; Viscor, Ginés; Roderick, Paul
Abstract : Introduction: About 5.7% of the world population resides above 1500 m. It has been hypothesised that acute exposure to high-altitude locations can increase stroke risk, while chronic hypoxia can reduce stroke-related mortality. Objective: This review aims to provide an overview of the available evidence on the association between long-term high-altitude exposure and ischaemic stroke. Design: A systematic review was performed from 1 January 1960 to 1 December 2021 to assess the possible link between high-altitude exposure and ischaemic stroke. The AMED, EMBASE, Cochrane Library, PubMed, MEDLINE, the Europe PubMed Central and the Latin-American bibliographic database Scielo were accessed using the University of Southampton library tool Delphis. In this review, we included population and individual-based observational studies, including cross-sectional and longitudinal studies except for those merely descriptive individual-based case reports. Studies were limited to humans living or visiting high-altitude locations for at least 28 days as a cut-off point for chronic exposure. Results: We reviewed a total of 1890 abstracts retrieved during the first step of the literature review process. The authors acquired in full text as potentially relevant 204 studies. Only 17 documents met the inclusion criteria and were finally included. Ten studies clearly suggest that living at high altitudes may be associated with an increased risk of stroke; however, five studies suggest that altitude may act as a protective factor for the development of stroke, while two studies report ambiguous results. Conclusions: This review suggests that the most robust studies are more likely to find that prolonged living at higher altitudes reduces the risk of developing stroke or dying from it. Increased irrigation due to angiogenesis and increased vascular perfusion might be the reason behind improved survival profiles among those living within this altitude range. In contrast, residing above 3500 m seems to be associated with an apparent increased risk of developing stroke, probably linked to the presence of polycythaemia and other associated factors such as increased blood viscosity.